2017
DOI: 10.1590/1678-4162-9115
|View full text |Cite
|
Sign up to set email alerts
|

Virulence, resistance, and genetic relatedness of Escherichia coli and Klebsiella sp. isolated from mule foals

Abstract: Respiratory diseases are common in young horses but little is known about such infections in mule foals. This study aimed to characterize Escherichia coli and Klebsiella sp. isolated from tracheal wash (TW) and fecal samples (FS) of mule foals, with or without cytological evidence of respiratory disease. Strains were analyzed against 13 antimicrobials, for presence of Extended spectrum beta-lactamase (ESBL), and virulence genes. Phylogrouping and Randomic (RAPD)-PCR profiles were used to evaluate their genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…The virulence factors associated with K pneumoniae were determined by targeting specific gene fimH encoding for type 1 fimbriae, the main virulence factor of the bacteria, using primer F 0 -ATGAACGCCTGGTCCTTTGC, R-GCT GAACGCCTATCCCCTGC, 26 and EntB gene responsible for enterobactin production using primer F-ATTTCC TCAACTTCTGGGGC and R-AGCATCGGTGGCGGT GGTCA. 27…”
Section: Molecular Detection Of Virulence Factorsmentioning
confidence: 99%
“…The virulence factors associated with K pneumoniae were determined by targeting specific gene fimH encoding for type 1 fimbriae, the main virulence factor of the bacteria, using primer F 0 -ATGAACGCCTGGTCCTTTGC, R-GCT GAACGCCTATCCCCTGC, 26 and EntB gene responsible for enterobactin production using primer F-ATTTCC TCAACTTCTGGGGC and R-AGCATCGGTGGCGGT GGTCA. 27…”
Section: Molecular Detection Of Virulence Factorsmentioning
confidence: 99%
“…Virulence genes characteristic of E. coli were also detected in non– E. coli strains. Carneiro et al (Carneiro et al 2017 ) observed the presence of fim H, pap C, and hly D virulence genes, which are usually detected in E. coli, also in K. pneumoniae strains from fecal samples. However, the prevalence of most virulence genes differed between non– E. coli and E. coli strains.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Carneiro et al . [ 46 ] reported that Klebsiella isolates were detected in 14.1% of 56 mule foals, primarily ampicillin-resistant, MDR, and ESBL producers. The bla SHV gene was more frequently found in K. pneumoniae isolates in Brazil.…”
Section: Discussionmentioning
confidence: 99%